PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS KONSTRUKTIVISME PADA MATERI KAIDAH PENCACAHAN UNTUK SISWA KELAS XI IS SMAN 3 LENGAYANG - Farianti, Gusfina - (Pendidikan Matematika, 2014)
The background of the research is the teaching material has not been able to helpthe students to construct the knowledge in finding the concept of teachingmaterial. The effect is the students tend to receive than to understand the learningconcept. The research aims to develop a valid and practical constructivism-basedof studentâs work sheet related to the material of enumeration rule. The type of theresearch is the development by using IDI model. IDI model consists of threedevelopment stages, i.e. define, develop, and evaluation. The validity test result ofstudentâs constructivism-based work sheet by validator is very valid, i.e. 3.51. Thestudent practical test result shows that constructivism-based work sheet is in thecategory of very practical, i.e. 81.25 % and the teacher practical test result is 76.78%, which is in the category of very practical. It can be concluded that studentâsconstructivism-based work sheet related to the material of enumeration rule isvery valid and practical.